2008
DOI: 10.1136/jech.2007.060798
|View full text |Cite
|
Sign up to set email alerts
|

When can group level clustering be ignored? Multilevel models versus single-level models with sparse data

Abstract: Multilevel models can be reliably estimated with an average of only five observations per group. Disaggregated techniques carry an increased risk of Type I error, even in situations where there is only limited clustering in the data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
222
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(240 citation statements)
references
References 30 publications
12
222
1
3
Order By: Relevance
“…It is likely, therefore, that reduced variance at patient level in models 3 and 4 is due to conflation of patient-and higher-level variance caused by clustering of patients within a small number of PCTs per Trust, a problem exacerbated by cross-classification in the data. 16, 22 We therefore considered that estimates of higher-level variance in Models 1 and 2 were more reliable than those of Models 3 and 4.…”
Section: Null (Unconditional) Modelsmentioning
confidence: 99%
“…It is likely, therefore, that reduced variance at patient level in models 3 and 4 is due to conflation of patient-and higher-level variance caused by clustering of patients within a small number of PCTs per Trust, a problem exacerbated by cross-classification in the data. 16, 22 We therefore considered that estimates of higher-level variance in Models 1 and 2 were more reliable than those of Models 3 and 4.…”
Section: Null (Unconditional) Modelsmentioning
confidence: 99%
“…Researchers employing simulation studies have found that the coefficients and standard errors produced by HLM are fairly robust to the sparse-data problem even in extreme situations (where the average number of cases at a level is two, and also even when singletons make up a fairly high proportion of cases). However, variance components at the group level may be biased upward and, likewise, the standard errors of the variance components, in particular, are likely to be biased upward, making it more difficult to detect significant group-level variation (Clarke, 2008). In light of this, we find it noteworthy that the chi-square test of significance for variation between tasks within teachers was significant for all of our academic language outcomes.…”
Section: Discussionmentioning
confidence: 80%
“…Simulation studies suggest that our fixed effects are not likely to be biased (Clarke, 2008). Furthermore, our analyses explained a fair amount of between-task and between-teacher variance even when cognitive demand and text quality were the only predictors in our models.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Absence of multicollinearity was confirmed by the fact that none of the model variables had zero-order correlations r  |0.5|. There was insufficient clustering of multiple jobs among individuals to support use of multilevel analysis [37]. Instead, data were weighted to reflect the number of jobs contributed by each individual [38].…”
Section: Discussionmentioning
confidence: 99%